Gestão do processo de desenvolvimento de produtos em clusters industriais: um survey no setor moveleiro da microrregião de Votuporanga-SP - Dias, Eliza Cristina (2011)
The Product Development Process (PDP) is a critical process because it is subject to innovation and competitive strategy of companies. The furniture industry of the micro-region of Votuporanga, consisting primarily of micro, small and medium sized companies is relatively new, and has a significant weight in the local economy, generating jobs and income. This research studies the PDP in the furniture sector of the micro-region of Votuporanga, placed in a cluster with the aim to identify the essential properties of this business process in order to establish its dynamic, technological and managerial vulnerabilities and strengths as well as the future prospects of the sector for meeting the challenges of competitiveness and innovation policy. From the scientific point of view, it draws a parallel between the theory and practice of product development in companies with limited manpower and financial resources. Thus, it considers the activity of the product development process in the context of the furniture industry as a study to attempt to confirm or refute hypotheses about the characteristics of PDP in small Brazilian companies. The descriptive and exploratory survey method was applied by a structured questionnaire with closed questions. The research instrument was developed and validated in a pilot study of ten companies. Statistical techniques were used to select the sample and analyze the data due to the large number of variables studied, so the statistical tools recommended and used were the descriptive and multivariate techniques. It was possible to confirm the weakness of the organizational structure of SMEs from the analysis and the constructs examined, wich generally adopt non-formal and imitative strategies with centralized administration based on owner s control. The success of the new product introductions depends on the tacit experience of those involved in product development.